2013
DOI: 10.1158/1078-0432.ccr-12-3258
|View full text |Cite
|
Sign up to set email alerts
|

Japonicone A Suppresses Growth of Burkitt Lymphoma Cells through Its Effect on NF-κB

Abstract: Purpose: NF-kB, a transcriptional regulator of diverse genes involved in cell survival, proliferation, adhesion, and apoptosis, has been implicated in various malignancies. We discovered a potent natural NF-kB inhibitor, Japonicone A, from the traditional herb Inula japonica Thunb, evaluated its preclinical pharmacology and therapeutic activity, and investigated the underlying mechanisms of action for its antitumor activity.Experimental Design: Various types of cancer and normal cells were exposed to Japonicon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…Traditional herbal medicines containing various biologically active natural compounds are believed to have therapeutic efficacy with minimal adverse effects [7]. Japonicone A is a natural product isolated from the aerial part of Inula japonica Thunb., which is a traditional medicine used to treat digestive disorders, bronchitis, inflammation, and bacterial and viral infections (including hepatitis) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional herbal medicines containing various biologically active natural compounds are believed to have therapeutic efficacy with minimal adverse effects [7]. Japonicone A is a natural product isolated from the aerial part of Inula japonica Thunb., which is a traditional medicine used to treat digestive disorders, bronchitis, inflammation, and bacterial and viral infections (including hepatitis) [8].…”
Section: Introductionmentioning
confidence: 99%
“…and antagonize its proinflammatory activities in vivo without impairing host antiviral immunity [9]. Further studies have demonstrated that japonicone A displayed potent anticancer effects on Burkitt lymphoma cells in vitro and in vivo through targeting the NF-κB signaling cascade [7]. However, the effects of japonicone A and its mechanism of action on human NSCLC cells have never been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability was determined with CCK-8 kits, as described previously (Li et al, 2013a, Li et al, 2013b). Briefly, cells were seeded in 96-well plates and were treated either with compounds at serial concentrations or for various times.…”
Section: Methodsmentioning
confidence: 99%
“…PI staining was used to detect the effects of ARS-related compounds on cell cycle distribution (Li et al, 2013a, Li et al, 2013b). In brief, after incubation with the compounds, A2780 and OVCAR3 cells were harvested and fixed with 70% ethanol, followed by RNase digestion and staining with PI (50 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Raji cells are a series of cell lines derived from B lymphocyte of a patient with Burkitt's lymphoma (BL) which is an aggressive form of B cell non Hodgkin's lymphoma [5] with reports of chemotherapy resistance.…”
Section: Introductionmentioning
confidence: 99%